Anxiety in visual field testing. Issue 8 (25th November 2015) - Chew, Shenton S L; Kerr, Nathan M; Wong, Aaron B C; Craig, Jennifer P; Chou, Chi-Ying; Danesh-Meyer, Helen V
Abstract : Background: To determine if Humphrey visual field (HVF) testing induces anxiety and how anxiety relates to visual field parameters of reliability and severity. Design: A prospective cohort study at a university affiliated private ophthalmic practice. Participants: 137 consecutive age-matched and gender-matched patients with glaucoma undergoing either HVF testing only (n=102) or Heidelberg retinal tomography (HRT) only (n=35) were enrolled. Methods: Prior to testing, participants completed the State-Trait Anxiety Inventory questionnaire. A 5-point Likert scale was used to grade pretest anxiety and was repeated after testing to grade intratest anxiety. Subjective discomfort parameters were also recorded. Main outcome measures: Anxiety scores were used to make non-parametrical comparisons and correlations between cohorts and also against visual field reliability and severity indices. Results: Trait anxiety (p=0.838) and pretest anxiety (p=0.802) were not significantly different between test groups. Within the HVF group, intratest anxiety was 1.2 times higher than pretest anxiety (p=0.0001), but was not significantly different in the HRT group (p=0.145). Pretest anxiety was correlated with test unreliability (Spearman's r=0.273, p=0.006), which was predictive of worse test severity (p=0.0027). Subjects who had undergone more than 10 visual field tests had significantly lower pretest and intratest anxiety levels than those who had not (p=0.0030 and p=0.0004, respectively). Conclusions: HVF testing induces more anxiety than HRT. Increased pretest anxiety may reduce HVF test reliability. Increased test experience or interventions aimed at reducing pretest anxiety may result in improved test reliability and accuracy.